Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(C=\dfrac{2^{2024}-3}{2^{2023}-1}=\dfrac{2.2^{2023}-2-1}{2^{2023}-1}=\dfrac{2\left(2^{2023}-1\right)-1}{2^{2023}-1}=2-\dfrac{1}{2^{2023}-1}\)
\(D=\dfrac{2^{2023}-3}{2^{2022}-1}=\dfrac{2.2^{2022}-2-1}{2^{2022}-1}=\dfrac{2\left(2^{2022}-1\right)-1}{2^{2022}-1}=2-\dfrac{1}{2^{2022}-1}\)
Ta có
\(2^{2023}>2^{2022}\Rightarrow2^{2023}-1>2^{2022}-1\)
\(\Rightarrow\dfrac{1}{2^{2023}-1}< \dfrac{1}{2^{2022}-1}\Rightarrow2-\dfrac{1}{2^{2023}-1}>2-\dfrac{1}{2^{2022}-1}\)
\(\Rightarrow C>D\)
A = \(\dfrac{1}{1+2+3}\)+\(\dfrac{1}{1+2+3+4}\)+...+ \(\dfrac{1}{1+2+...+2004}\)+ \(\dfrac{2}{2025}\)
A = \(\dfrac{1}{\left(1+3\right).3:2}\)+\(\dfrac{1}{\left(4+1\right).4:2}\)+...+ \(\dfrac{1}{\left(2024+1\right).2024:2}\)+\(\dfrac{2}{2025}\)
A = \(\dfrac{2}{3.4}\)+\(\dfrac{2}{4.5}\)+...+\(\dfrac{2}{2024.2025}\)+ \(\dfrac{2}{2025}\)
A = 2.(\(\dfrac{1}{3.4}\) + \(\dfrac{1}{4.5}\)+...+ \(\dfrac{1}{2024.2025}\)) + \(\dfrac{2}{2025}\)
A = 2.(\(\dfrac{1}{3}\) - \(\dfrac{1}{4}\) + \(\dfrac{1}{4}\) - \(\dfrac{1}{5}\)+...+ \(\dfrac{1}{2024}\) - \(\dfrac{1}{2025}\)) + \(\dfrac{2}{2025}\)
A = 2.(\(\dfrac{1}{3}\) - \(\dfrac{1}{2025}\)) + \(\dfrac{2}{2025}\)
A = \(\dfrac{2}{3}\) - \(\dfrac{2}{2025}\) + \(\dfrac{2}{2025}\)
A = \(\dfrac{2}{3}\)
1+1/2.(1+2)+1/3.(1+2+3)+1/4.(1+2+3+4)+...+1/2023.(1+2+3+...+2023)
=1+1/2.(1+2).2/2+1/3.(1+3).3/2+1/4.(1+4).4/2+...+1/2023.(1+2+3+...+2023).2023/2
=2/2+3/2+4/2+...+2023/2
=2+3+4+...+2023/2
=2025.2022/2/2
=1023637,5
a) 49.(-34)+(-65).49-49 = 49. (-34-65-1)= 49. (-100)= -4900
b) -268-(-47-168)-147 = (-268 + 168) - (147 - 47)= -100 -100=-200
c) (-2)2.(-3)-[(-1)2024+8]:(-3)2 = 4. (-3) - [1 +8]:9 = -12 - 9:9 = -12 - 1 = -13
d) 67-[8+7.32 -24:6+(9-7)3]:15 = 67 - [8 + 7.9 - 4 + 23 ] : 15
= 67 - [8+63-4+8]:15 = 67 - 75:15 = 67 - 5 = 62
\(S=1+3^2+3^4+...+3^{2022}\)
\(3^2S=9S=3^2+3^4+3^6+...+3^{2024}\)
\(S=\dfrac{9S-S}{8}=\left(3^{2024}-1\right):8\)
d, không đáp án nào đúng
Lời giải:
$S=1+3^2+3^4+....+3^{2022}$
$9S=3^2S=3^2+3^4+3^6+...+3^{2024}$
$\Rightarrow 9S-S=3^{2024}-1$
$\Rightarrow S=\frac{3^{2024}-1}{8}$
Đáp án D.
A=1+2 +22+.....+22024
2A=2(1+2 +22+.....+22024)
2A=2+22 +23+.....+22025
2A-A=(2+22 +23+.....+22025)-(1+2 +22+.....+22024)
A=22025-1
\(D=2+2^2+2^3+...+2^{2024}\)
\(2D=2^2+2^3+2^4+...+2^{2025}\)
\(2D-D=\left(2^2+2^3+2^4+...+2^{2025}\right)-\left(2+2^2+2^3+...+2^{2024}\right)\)
\(D=2^{2025}-2\)
Vậy....
D = 2 + 2² + 2³ + ... + 2²⁰²⁴
2D = 2² + 2³ + 2⁴ + ... + 2²⁰²⁵
D = 2D - D
= (2² + 2³ + 2⁴ + ... 2²⁰²⁵) - (2 + 2² + 2³ + ... + 2²⁰²⁴)
= 2²⁰²⁵ - 2